2017
DOI: 10.1038/bjc.2017.270
|View full text |Cite
|
Sign up to set email alerts
|

Nintedanib selectively inhibits the activation and tumour-promoting effects of fibroblasts from lung adenocarcinoma patients

Abstract: Background:Nintedanib is a clinically approved multikinase receptor inhibitor to treat non-small cell lung cancer with adenocarcinoma (ADC) histology in combination with docetaxel, based on the clinical benefits reported on ADC but not on squamous cell carcinoma (SCC), which are the two most common histologic lung cancer subtypes.Methods:We examined the potential role of tumour-associated fibroblasts (TAFs) in the differential effects of nintedanib in ADC and SCC. Because TAFs are largely quiescent and activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 44 publications
3
39
0
Order By: Relevance
“…Stromal TAFs have been implicated in virtually all steps of tumor progression [7]. Therefore it is unsurprising that stromal proteins, including those related to TAFs, are receiving increasing interest as biomarkers or therapeutic targets [9,30]. However, the prognostic value of standard markers of activated TAFs had remained ill defined in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stromal TAFs have been implicated in virtually all steps of tumor progression [7]. Therefore it is unsurprising that stromal proteins, including those related to TAFs, are receiving increasing interest as biomarkers or therapeutic targets [9,30]. However, the prognostic value of standard markers of activated TAFs had remained ill defined in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…This desmoplastic stroma is rich in activated fibroblasts (referred to as cancer-or tumorassociated fibroblasts (TAFs)), infiltrated immune cells and other less frequent cell types, in the background of an abundant deposition of fibrillar collagens and other fibrotic extracellular matrix components [4,5]. Of note, TAFs are largely responsible for the aberrant stromal deposition of fibrillar collagens within the tumor stroma [6], and are receiving increasing interest as a therapeutic target [7], as illustrated by the recent approval of the antiangiogenic and antifibrotic drug nintedanib to treat lung ADC patients in combination with docetaxel [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Antifibrotic drugs are thought to be candidates for targeting CAF because of their ability to suppress fibroblast activity. Actually, recent studies have shown that pirfenidone and the multi‐kinase inhibitor, nintedanib, which are drugs to treat idiopathic pulmonary fibrosis, can inhibit cancer progression through suppression of CAF in pancreatic cancer, breast cancer, and lung adenocarcinoma . It was reported that pirfenidone and nintedanib suppressed TGF‐β signaling and production of extracellular matrix components in tumor‐stromal interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Pirfenidone ( 1 , Esbriet®) and nintedanib ( 2 , Ofev®) are the only two drugs that have been approved by the U.S. Food and Drug Administration (FDA) for the treatment of IPF. Pirfenidone works by reducing lung fibrosis through downregulation of the production of growth factors and procollagens I and II, while nintedanib, is a well‐known multiprotein tyrosine kinase (PTK) inhibitor, which can inhibit the enzymatic activity of VEGFR1, VEGFR2, VEGFR3, FGFR1, FGFR2, FGFR3, PDGFα, and PDGFβ . GLPG1690 ( 3 ), a recently discovered autotaxin inhibitor, showed great efficacy in a bleomycin(BLM)‐induced pulmonary fibrosis model in mice and in reducing extracellular matrix deposition in the lung.…”
Section: Figurementioning
confidence: 99%
“…Pirfenidone works by reducing lung fibrosis through downregulation of the production of growth factors and procollagens I and II, [7,8] while nintedanib, is a wellknown multiprotein tyrosine kinase (PTK) inhibitor, which can inhibit the enzymatic activity of VEGFR1, VEGFR2, VEGFR3, FGFR1, FGFR2, FGFR3, PDGFα, and PDGFβ. [9][10][11] GLPG1690 (3), [12] a recently discovered autotaxin inhibitor, showed great efficacy in a bleomycin(BLM)-induced pulmonary fibrosis model in mice and in reducing extracellular matrix deposition in the lung. GLPG1690 is now currently being evaluated in an exploratory phase III study in idiopathic pulmonary fibrosis patients (ClinicalTrials.gov Identifier: NCT03733444) ( Figure 1).…”
Section: Novel Pyrimidines As Multitarget Protein Tyrosine Kinase Inhmentioning
confidence: 99%